2015
DOI: 10.1590/2175-7860201566205
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de diversidad de la familia Poaceae en la región austral de America del Sur

Abstract: Este artículo tiene material adicional en la versión electrónica. ResumenAnálisis de diversidad de la familia Poaceae en la región austral de América del Sur. La familia Poaceae es una de las mejor representadas en América del Sur austral, con un total de 206 géneros que comprenden 1523 especies distribuidas en 10 subfamilias diferentes. En este trabajo analizamos la distribución de estos grupos en Argentina, sur de Brasil (Paraná, Rio Grande do Sul y Santa Catarina), Chile, Paraguay y Uruguay; discutimos la r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…Grass species grown in South American grasslands play key role in forage production due to the large number of species and efficient dry matter production (Biganzoli and Zuloaga, 2015). This feature was observed in the present study, since the largest number of identified species belonged to family Poaceae and accounted for more than 65% of produced dry matter, regardless of the treatment (data not shown).…”
Section: Changes In Vegetation Compositionsupporting
confidence: 68%
“…Grass species grown in South American grasslands play key role in forage production due to the large number of species and efficient dry matter production (Biganzoli and Zuloaga, 2015). This feature was observed in the present study, since the largest number of identified species belonged to family Poaceae and accounted for more than 65% of produced dry matter, regardless of the treatment (data not shown).…”
Section: Changes In Vegetation Compositionsupporting
confidence: 68%
“…Desv., Piptochaetium J.Presl and Chascolytrum Desv. (Biganzoli & Zuloaga, ) among the most species‐rich genera — never reach abundance levels as high as those of the dominating C4 grasses, but they can be particularly abundant during early spring, before most C4 species starts their regrowth. This also explains their importance for cattle grazing management, since these species provide high‐quality biomass at a period when the C4 species are still not very productive due to low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…La familia Poaceae, es de distribución cosmopolita, de regiones tropicales y templadas; comprende aproximadamente 700 géneros y 11.000 especies, son dominantes en una gran diversidad de ecosistemas, además de poseer una gran importancia económica para el hombre (Chen et al, 2006;Zuloaga, Rugolo y Anton, 2012). Las Poaceaees una de las 4 familias con mayor número de especies de plantas vasculares (Biganzoli y Zuloaga, 2015). El género Guadua comprende 31 especies que habitan regiones tropicales y sub tropicales de América Central y del Sur (Zuloaga, Rugolo y Anton, 2012).…”
Section: Resultados Y Discusiónunclassified